The Effect of Basalt Fiber on the Performance of Stone Mastic Asphalt - Çetin, Altan; Evirgen, Burak; Karslioglu, Asena; Tuncan, Ahmet; Çetin, Altan (Budapest Univ Technology Economics, 2020)
Stone Mastic Asphalt (SMA) is a mixture design against rutting caused by intensive and heavy traffic loads. While modified bitumen needs to be used in this mixture, the use of cellulosic fibers is essential to prevent the infiltration of bitumen during the carriage of mixture due to high bitumen content. In this study, the effects of basalt fiber on the performance of SMA mixtures is investigated as an alternative to cellulosic fiber admixtures in the prevention of draindown. Raw materials commonly used in Turkey were chosen as Type-I graded limestone aggregate and B50/70 asphalt cement, according to the General Directorate of Highways. In total, 109 specimens were prepared by a gyratory compactor according to the superpave design method. Sixty of these specimens were basalt fiber added samples with a ratio from 0.1 % to 0.8 % by dry weight aggregate. An addition of basalt fiber of 0.6 % at 25 degrees C seriously increases the resilient modulus and tensile strength of the samples. In addition, 0.4 % basalt fiber mixed samples shows that the greatest resistance against permanent deformation according to the results of static uniaxial creep test performed at 40 degrees C. Basalt fibers have no positive effect when a decrement of bitumen viscosity exceeds the bitumen softening point at the end of repeated uniaxial tests. On the other hand, bitumen draindown and water damage test results are within acceptable limits.
Keywords: Stone Mastic Asphalt; Basalt Fiber; Resilient Modulus; Bitumen Draindown; Permanent Deformation